Phosphorus and liming effects on early growth of selected plant species grown on an Ultisol - Kang, B.; Ladipo, D.O.; Ofeimu, O. (Informa UK Limited, 1995)
A series of pot experiments were conducted to test the effect of phosphorus (P) application and liming on early growth performance of Zea mays, Mucuna pruriens and nine woody species (Albizia ferruginea, Cajanus cajan, Dactyladenia barteri, Dalbergia sissoo, Enterolobium cyclocarpum, Flemingia macrophylla, Gliricidia sepium, Leucaena leucocephala, and Pentacletra macrophylla) on an Ultisol. Low reponse to liming and high response to P application were observed in this trial. Early top growth of the eleven species was correlated to seed size and seed nitrogen (N), P, and calcium (Ca) contents. Highest correlation was observed with seed P content (r = 0.896**). Large seeded size species (D. barteri, E. cyclocarpum, M. pruriens, and P. macrophylla) showed the least reponse to P application, while the remaining small seeded size species showed significant responses to P application. The large seeded species also showed relatively less increases in N, P and Ca uptakes with P application and liming. The pot test can be used in prescreening of woody species for use on low P and acid soils. The results also emphasize the need for seed size consideration in multipurpose trees and shrubs selection for establishment in low P and on degraded soils.